The U.S. cable televisions' framing of mass shooting: a grounded discovery of competing narratives - Emelu, Maurice N. (Frontiers in Communication, 2023)
News frames play a vital role in shaping the audience's interpretation of the news, their participation in policy discussions, and their engagement in public discourse. This study uses the Analysis of Topic Model Networks (ANTMA) frame analysis grounded approach and examines the 2017 Sutherland Springs, Texas, mass shooting coverage in a house of worship by three U.S. cable television networks—CNN, Fox News, and MSNBC. News reports for the first seven days following the shooting were collected from the cable networks' Twitter, YouTube, and website accounts. A total of 290 news reports were analyzed and 760 aggregate units for frames were coded. The results demonstrate that ANTMA grounded approach is an effective method for frame analysis and support research about the news media's emphasis on victims, community, and individual frames in cases of mass shootings. They identify differences in the issue-based frame of gun vs. mental health debates. Additional new frames of empathy, interventions, reactions, and security were discovered. Results also show differences in frames used and their frequency between the digital platforms of Twitter, YouTube, and websites and cable organizations. These differences show each media network's ideological perspectives or competing news narratives. The findings raise relevant questions to news coverage, policy debates about mental health and gun violence, and cultural awareness of the problem of mass shootings and public safety as the world becomes more global.